A POLITICAL ETHICS IN FIQH SIYASAH: A STUDY ON THE PRINCIPLES OF MORALITY IN POLITICS - Qotimatun Puji Rahayu, Fadilah (Program Studi Hukum Tata Negara, 2025)
Ethics plays an important role in the world of politics, especially in the contemporary political context which is often filled with practices that violate norms and ethics. Fiqh, as a discipline that studies Islamic laws, offers ethical guidance in politics. This research focuses on the application of political ethics in Fiqh in a contemporary political context. The Problem Although Fiqh offers guidance on political ethics, its application in contemporary political contexts often encounters challenges, such as highly competitive political systems and differing interpretations of what is considered ethical. This study uses literature research methods, through critical and systematic analysis of various relevant sources of literature on political ethics in Fiqh. The conclusion of this study is that ethical principles in Fiqh, such as fairness, honesty, consultation (shura), and accountability, can help shape politics that is more just, responsible, and oriented to the public interest. However, applying these principles requires a deep understanding of Fiqh and the contemporary political context, as well as a strong commitment to ethics and justice.